Dyslipidemia profiles and their sex-dimorphic impact on cardiometabolic risk in Arab adolescents - Al-Daghri, Nasser M.; Alfawaz, Hanan A.; Khattak, Malak N. K.; Khan, Nasiruddin (Frontiers in Pediatrics, 2025)
PurposeRecently, the prevalence of dyslipidemia has been on the rise among Saudi children and adolescents. Although dyslipidemia is a well-established cardiovascular disease (CVD) risk factor, the strength of its associations relative to other cardiometabolic risk factors, particularly in the pediatric population, remains unclear. This study aims to identify the associations of both single and combined lipid abnormalities, obesity status and CVD risk factors among Saudi adolescents.MethodsThis cross-sectional study included 4,930 adolescents [1,773 boys [mean age 14.6 ± 1.6] and 3,157 girls [mean age 14.4 ± 1.6]]. Dyslipidemia was defined based on the National Heart Lung and Blood Institute and National Cholesterol Education Program guidelines for adolescents.ResultsOverall, 46.5% had at least one abnormal lipid profile level, while 18.6% and 2.6% exhibited changes in two or all lipid profile variables, respectively. The most common lipid abnormalities were borderline to high triglycerides and low HDL-C levels. Regardless of gender, higher BMI was associated with more significant changes in lipid profile parameters. The boys with hyperglycemia was found to be significantly associated with more altered combined dyslipidemia than girls.ConclusionsDyslipidemia patterns related to obesity are commonly observed in Arab adolescents. Therefore, it is imperative to implement public health interventions that prioritize school-based physical education initiatives and lipid management strategies for this population.